(untitled) (Global Conference on Medical and Health Sciences, 2026)
Reproductive dysfunction in pubertal girls remains one of the most relevant problems in pediatric gynecology and endocrinology, as it develops during the critical period of maturation of the hypothalamic-pituitary-ovarian axis and may substantially influence future reproductive potential. Menstrual disorders associated with abnormalities in body mass index (BMI) are of particular importance, since both obesity and underweight can significantly affect the tempo of pubertal development, the establishment of ovulatory function, hormonal homeostasis, and the morphofunctional characteristics of the reproductive organs. During puberty, alterations in metabolic status often become one of the key factors contributing to the development of amenorrhea, opsomenorrhea, acyclic uterine bleeding, and other menstrual disturbances. Therefore, the study of clinical, hormonal, and instrumental features of reproductive dysfunction in adolescent girls according to BMI is of clear scientific and practical relevance.